2009
DOI: 10.1180/minmag.2009.073.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Preferred ion diffusion pathways and activation energies for Ag in the crystal structure of stephanite, Ag5SbS4

Abstract: The crystal structure of stephanite fromthe type locality, Freiberg District, Saxony, Germany, was refined in the space group Cmc21, up to a final R index of 0.0427. Unit-cell parameters are: a 7.8329(6) Å, b 12.458(1) Å, c 8.5272(7) Å, V 832.1(1) Å3; Z = 4. The previously reported structural model is confirmed, but a higher-precision refinement was achieved herein by the introduction of thirdorder non-harmonic Gram-Charlier tensors for one Ag atom. In the structure of stephanite, Sb forms isolated SbS3 pyrami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Although Leitl et al (2009) confirmed the main structural features previously reported, they also introduced new aspects. For example, one of the silver positions was refined by using non-harmonic parameters of the third order according to Gram-Charlier (Zucker & Schulz, 1982).…”
Section: Figuresupporting
confidence: 85%
See 3 more Smart Citations
“…Although Leitl et al (2009) confirmed the main structural features previously reported, they also introduced new aspects. For example, one of the silver positions was refined by using non-harmonic parameters of the third order according to Gram-Charlier (Zucker & Schulz, 1982).…”
Section: Figuresupporting
confidence: 85%
“…The latter authors used this mineral as an example to show to the mineralogical community that the non-harmonic approach, based upon a Gram-Charlier development of the atomic displacement factors, can be useful in mineral sciences for the determination of still unknown structures. The same approach was then used by Leitl et al (2009) to describe the crystal structure of stephanite, Ag 5 SbS 4 .…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Ag + and Cu + ions), which can result in the formation of various complex asymmetric coordinations often producing overlapping sites (Gaudin et al ., 2001). Classic examples of this kind of mineral are samsonite, Ag 4 MnSb 2 S 6 (Bindi and Evain, 2007), stephanite, Ag 5 SbS 4 (Leitl et al ., 2009), pearceite–polybasite group minerals, [(Ag,Cu) 16 M S 11 where M = Sb or As] (i.e. Bindi et al .…”
Section: Resultsmentioning
confidence: 99%